Characterization of atmospheric corrosion near the coastal areas of Arabian Sea. Issue 7 (29th December 2017) - Jamil, Ishrat; Bano, Humaira; Castano, Juan G.; Mahmood, Azhar
Abstract : Atmospheric corrosion near the coastal areas of Karachi is a subject of great interest where seasonal variation of north Arabian Sea, high onshore activities, high levels of atmospheric pollutants, high humidity, and low temperature range affects the service life of structural materials. Mild steel test coupons were exposed at the two atmospheric corrosion stations located in National Institute of Oceanography (NIO) and Karachi Port Trust (KPT) along the coastal line of Karachi, Pakistan for a period of 12 months. During the exposure period, the sulfur dioxide and chloride levels, corrosion rates and kinetics parameters were determined. The corrosion rates are high on both sites, but the corrosivity found in NIO is higher (C5) than in KPT (C4). Scanning electron microscopy/energy dispersive X‐ray spectroscopy (SEM/EDS), Fourier transform infrared (FTIR) spectroscopy, and X‐ray diffraction (XRD) were used to characterize the corrosion products. Lepidocrocite is the main compound in NIO corrosion products, while in KPT are goethite and magnetite. The composition and morphology of corrosion products help to explain the difference in the corrosivity of both sites. Abstract : Mild steel test coupons were exposed at two atmospheric corrosion stations located along the coastal line of Karachi, Pakistan for a period of 12 months. During the exposure period, the sulfur dioxide and chloride levels, corrosion rates and kinetics parameters were determined. The composition and morphology of corrosion products help to explain the difference in the corrosivity of both sites.